Unraveling the Connections: Exploring the Relationship between Teaching Effectiveness and Academic Achievement in Blended Learning Environments - Karen A. Manaig; Alberto D. Yazon; John Frederick B. Tesoro; Chester Alexis C. Buama; Sherwin B. Sapin (Advanced Journal of STEM Education, 2024)
With the rise of blended learning, assessing the factors influencing student academic performance has become essential. Teaching effectiveness is a critical component of this dynamic, potentially affecting students’ academic success. This study examines the relationship between teaching effectiveness and the academic performance of students engaged in blended learning environments. The primary objective of this research was to determine whether a significant relationship exists between teaching effectiveness and student academic performance. Specifically, this study evaluated various aspects of teaching effectiveness, including the learning environment and instructional practices, and their impact on student achievement. A descriptive-correlational research design was employed, using Simple Random Sampling to select 297 student respondents from the records provided by the university registrar’s office. The study measured teaching effectiveness using the university’s standardized School Form (SF) 7, while students’ academic performance was gauged via their general weighted average for the 2022-2023 academic year. Data analysis included calculating the mean and standard deviation to determine the levels of teaching effectiveness and academic performance, with Pearson’s r used to assess the correlation between these variables. The results indicated that the learning environment aspect of teaching effectiveness scored the highest, while instructional and assessment practices scored the lowest. Overall, teaching effectiveness was rated "Very Satisfactory." A significant positive correlation was identified between teaching effectiveness and student academic performance, thus contradicting the null hypothesis. The findings underscore a strong, consistent positive relationship among the various dimensions of teaching effectiveness, revealing that effective teaching in one area is linked with higher effectiveness in others. This interconnectedness highlights the importance of a comprehensive approach to enhancing teaching practices and suggests that improvements in teaching effectiveness can lead to better academic outcomes in blended learning contexts.